2022
DOI: 10.32604/cmc.2022.019420
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Automatic Translation of Text to Sign Language

Abstract: Communication is a basic need of every human being; by this, they can learn, express their feelings and exchange their ideas, but deaf people cannot listen and speak. For communication, they use various hands gestures, also known as Sign Language (SL), which they learn from special schools. As normal people have not taken SL classes; therefore, they are unable to perform signs of daily routine sentences (e.g., what are the specifications of this mobile phone?). A technological solution can facilitate in overco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Thus, our hypothesis 2a which states that there is a significant positive effect of growth opportunities on corporate sustainable growth is supported. This finding is also in conformity with prior studies such as Sanaullah, Sheraz, and Kashif, [21] and Chashmi and Fadaee [6].…”
Section: Data Analysis and Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our hypothesis 2a which states that there is a significant positive effect of growth opportunities on corporate sustainable growth is supported. This finding is also in conformity with prior studies such as Sanaullah, Sheraz, and Kashif, [21] and Chashmi and Fadaee [6].…”
Section: Data Analysis and Resultssupporting
confidence: 93%
“…In this study, the association between COVID-19 and corporate sustainable growth is projected to be moderated by growth opportunities. Previous studies [21,6] have shown that growth opportunity is a critical success factor for profitability and economic valued added of the firm. Andawasatya, Indrawati, and Aisjah [3] provide evidence that the improvement of opportunities for growth, profitability, and firm size significantly improve firm value.…”
Section: Covid-19 Pandemic and Corporate Sustainable Growth: The Mode...mentioning
confidence: 99%
“…5 Related work based on HamNoSys: Morrissey (2011); Sanaullah et al (2021); Walsh et al (2022) 21/06/2022, 14:40 https://raw.githubusercontent.com/sign-language-processing/sign-language-processing.github.io/eddb4ac50ffc7698d4b2b9c8c34d6397721… https://raw.githubusercontent.com/sign-language-processing/sign-language-processing.github.io/eddb4ac50ffc7698d4b2b9c8c34d63977211602c/src/assets/tasks/… 1/1…”
Section: Motivationmentioning
confidence: 99%
“…Ref. [85] developed the Sign4PSL database containing 400 basic signs of PSL and manual features only. These included alphabets, numbers, 40 words, and 25 sentences.…”
Section: Srq2c: Sign Language Corpora Characteristics and Annotation ...mentioning
confidence: 99%